Phacoemulsification and intraocular lens implantation after inadvertent intracapsular injection of intravitreal dexamethasone implant. (12th December 2012) - Ram, Jagat; Agarwal, Aniruddha Kishandutt; Gupta, Adit; Gupta, Amod
Abstract : In this interventional case series, two eyes of two patients with diabetic macular oedema and one eye of a patient with complicated cataract secondary to uveitis associated with juvenile idiopathic arthritis had inadvertent injection of dexamethasone implant into the capsular bag. This was followed by successful completion of phacoemulsification and intraocular lens implantation. At 1-year follow-up, all patients maintained visual acuity of ≥20/40 with absence of macular oedema.